STUDI KASUS: ASUHAN KEPERAWATAN PADA PASIEN DENGAN ASFIKSIA NEONATORUM - Derma Wani Damanik; Julwansa Saragih; Riris Artha Dhita Purba (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2021)
Background: Neonatal asphyxia is a condition in which the baby cannot breathe spontaneously and regularly after birth, caused by fetal hypoxia in the uterus. Objective: This study aims to determine nursing care in patients with asphyxia neonatorum. Methods: this study used a descriptive method with an approach through the management of nursing care of By R aged 0 days. Results: this study was conducted at the Army Hospital TK IV 010701 Pematangsiantar in April 2021. Data collection was carried out through interviews with patients' families and nurses. Based on the assessment, the data obtained from the baby with a frequency of 68x/minute, apgar score 5/6, irregular breathing rhythm, chest retractions, using respiratory accessory muscles, yellowish eyes and skin, dark yellow urine, pale stools, body temperature 37.5 C, elevated bilirubin and leukocyte values. After nursing actions for 4 days all problems were resolved. Conclusion: Implementation is carried out according to the plan prepared so that the three nursing problems can be resolved.